(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
This study aims to determine the implementation of credit agreements on savings and loans at cooperatives based on the Civil Code. As well as to find out obstacles in the process of credit agreement for savings and loans at the Mallomo Jaya Abadi Cooperative in Makassar City. This study uses an empirical legal research method, namely legal research that focuses on research on legal realities in society. The results of this study indicate that the implementation of the agreement between parties is very easy. Cooperative members only submit guarantees in accordance with the goods that have been determined by the Savings and Loan Cooperative (KSP). Inhibiting factors in the process of credit agreements for savings and loans at the Mallomo Jaya Abadi Cooperative in Makassar City are due to profession and default. In resolving a dispute if a member of the Cooperative fails, the management of the Mallomo Jaya Abadi Cooperative will go to the member of the cooperative and ask the problem why the cooperative member cannot pay his loan. The recommendation of this research is that the Mallomo Jaya Abadi Cooperative should take into account the value of the guarantee more carefully so that if the members of the Cooperative make arrears for a long time, the guarantee value can still cover the principal debt and costs for the delay and it is expected that the Mallomo Jaya Cooperative The perpetrator must be more assertive in implementing the contents of the agreement and taking action against cooperative members who violate the agreement according to the law, namely gradually giving a warning in accordance with the agreement, both an oral warning and a written warning.